Analisis Kadar Air Benih Kedelai (Glycine max) Varietas Anjasmoro Menggunakan Metode Oven - Jamaluddinsyah, Jamaluddinsyah; Hidayat, Muslich; Rija Arhas, Firman (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2026)
Moisture content is a pivotal parameter determining the viability and storage life of soybean seeds. This study aimed to evaluate the moisture content of Anjasmoro variety soybean (Glycine max) seeds using the constant high-temperature oven method. The research was conducted at the UPTD BPSBTPHP Laboratory in Banda Aceh. The methodology employed drying ground seed samples in an oven at 130°C–133°C for a duration of one hour. The experimental results revealed an average moisture content of 10.2095% derived from two replicates. This value falls within the recommended safe threshold for soybean seed storage, which ranges between 10% and 12%. Consequently, the tested seeds are categorized as having high physical quality and are suitable for long-term storage without significant risk of biological deterioration. Keywords: moisture content; seed quality; glycine max